Treatment of Multiple Antibiotic Resistant Pseudomonas with DMSO to Revert Resistance - Dr. M. Razia; Dr. Madhumita Ghosh Dastidar (International Journal of Pharma and Bio Sciences, 2020)
Multiple drug-resistant (MDR) bacteria are resistant to various classes of antibiotics which causes concern in social health issues. Such an organism – Pseudomonas aeruginosa was isolated from the hospital environment. Drug resistance concerning different classes of antibiotics was tested. It was found that bacteria were resistant to most antibiotics. The resistant bacteria were treated with Dimethyl sulfoxide (DMSO) to observe the effect of DMSO on resistant bacteria. DMSO showed a synergistic along with antibiotics in inhibiting the growth of Pseudomonas aeruginosa. It was observed that the percentage of protein concentration was decreased by 20% in the presence of 0.5% DMSO and 40% decreased in the presence of 1% DMSO. The SDS-PAGE analysis showed the appearance of protein bands at 97.4 KDa in antibiotic-resistant Pseudomonas but the same disappeared completely when treated with DMSO. This study revealed that DMSO has a potential effect in reversing the antibiotic resistance in Pseudomonas by affecting the membrane protein of the bacteria.